X-linked Charcot-Marie -Tooth neuropathy: mutation and haplotype analyses - Akat, İrem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Charcot-Marie-Tooth disease is the most common peripheral neuropathy with a prevalence of 17-40 per 100.000 individuals. X-linked Charcot-Marie-Tooth (CMTX) disease accounts for up to 15% of all CMT cases. There are five known loci for CMTX (CMTX1, CMTX2, CMTX3, CMTX5 and Cowchock Syndrome). To date only genes for CMTX1 (GJB1/Cx32) and CMTX5 (PRPS1) have been identified. In this study, 23 CMT families and 72 isolated CMT cases were analyzed. A combination of SSCP, high resolution melting analysis and sequencing was used to screen the cohort for GJB1/Cx32 mutations. In ten patients, nine different mutations, two of which were novel, have been identified. The incidence of Cx32 mutations in our cohort was found to be 10%. Ten families were selected for haplotype analysis according to clinical criteria and pedigree analysis. After exclusion of PRPS1 mutations in these families, we investigated linkage to CMTX2, CMTX3 and CMTX4 loci. The analyses revealed linkage to CMTX2 in two, CMTX3 in one, and to CMTX4 in one other family. PRPS2 gene was screened as a candidate gene in two CMTX2 families. The patients tested negative for causative mutations but two common polymorphisms were identified. Linkage to known X-linked recessive loci was excluded in six families. This study is the first on X-linked recessive CMT in Turkish population. It is important to show further evidence for the involvement of previously identified X-linked recessive CMT loci. The families excluded for all known loci reveals further genetic heterogeneity of X-linked CMT.
Keywords: Charcot-Marie-Tooth disease.; X-linked mental retardation.